A relação do Capital Intelectual e seu disclosure no crescimento da firma - Steinke, Aline (2020)
This study is based on the premise that Intellectual Capital (CI) and CI disclosure contribute to Firm Growth from the perspective of Penrose (2006). Thus, the study aims to evaluate the relationship between investments in Intellectual Capital and its disclosure in the Growth of Brazilian Firms. The methodology used is characterized as descriptive with documentary character, the predominant quantitative approach and data analysis through descriptive statistics and panel data analysis. Previous studies and the results themselves indicated that it is better to analyze the influence of Value Added. Intellectual Coefficient (VAIC), on the growth of firms, considering their components separately, as they have differentiated influences. It is possible to conclude that VAHU had the best result on the companies growth, according to the metrics useded, and disclosure of intellectual capital can improve the coefficients of VAHU and VACE. In spite of this, observing the average of the indices of the components of the VAIC, a decrease is noted over the time of the VAHU and VACE, indicating that, despite having a positive result on companies, they have invested less in these two types of capital and started to invest more in STVA, which did not present positive results in any of the models in this research.